Supra Continuous $\breve{g}$ in Topological Spaces - S. Usharani (International Journal of Mathematics And its Applications, 2018)
The aim of this paper is to introduce and investigate a new class of sets and functions between topological space called supra $\breve{g}$-open sets and supra $\breve{g}$-closed functions respectively, furthermore introduced the concept of supra $\breve{g}$-open mapping and supra $\breve{g}$-closed maps and investigated several properties of them. Additionally, we relate and compare these functions with some other functions in topological spaces.